An Investigation of Intestinal Parasitic Infections Among the Asymptomatic Children in, Southern Ethiopia - Unasho, Abayneh (International Journal of Child Health and Nutrition, 2013)
Background: Children under five years, particularly aged 2-4 years (24-48 months), are more vulnerable to intestinal parasitic infections. This is because, children with this ages may contract infective agents during their intense activities, and adventures such as crawling or walking on bare ground, sand or grasses or eating mud/pica. Increased population density, lack of awareness, poor sanitation, and poor public health practices, and environmental sanitations, affect the prevalence of parasitic infection in tropical countries. Moreover, the prevalence of intestinal parasitic infections among the asymptomatic children aged under five is not well studied. Objectives: The objectives of this study was to investigate the prevalence of intestinal parasitic infections among the asymptomatic children aged 6-59 months in selected Southern Ethiopia including Gedeo, Amaro, Walyta and Kambata. Methods: A cross-sectional study was carried out and the sampling design combined multistage sampling methods including, both simple random sampling technique, population density and systematic random sampling techniques. The course of this study took over a period of 5 months, from September 2009 to January 2010. Study participants were estimated by convenient sampling method to include 406 asymptomatic children (217 females and 189 males) from the systematically selected households of the study sites. Parasitological diagnosis of the parasites was done using the standard parasite and ova method. A total of 406 stool specimens were examined by a direct microscopy using a normal saline (0.9%) and lugol’s iodine wet mount techniques to determine the infection of intestinal parasites and the analysis of the data was made manually using thematic framework method. Results: Of the total 406 study participants, 170 (41.9%) children were found to have single and double intestinal parasitic infections whilst 236 (58%) children were free from the suspected parasites. Ascaris, lumbricoides, amoeba spp, Giardia lamblia, Trichuris trichiura, hookworms spp, Strongyloides stercoralis, and Hymenolepis nana were identified in both single and double infections. Double infections were found in 19 (11.2%) asymptomatic children of the total positive cases and the rest were single infections. In both single and double infections, ascaris was found to be the most dominant infective agent accounted 111(59%) out of the total 187 parasitic load of infection, followed by amoeba spp.31 (16.6%) and Trichuris trichiura 17(9%). Higher proportions of infected age groups were 25-48 while the least infected age groups were 6-24 and 49-59 months. Concluding Remarks and Recommendations: This baseline study indicated higher prevalence of intestinal parasitic infections in the study area and therefore, much effort is remaining to fight against parasitic infection. Along with regular deworming intervention, health education including infection cycle, environmental sanitation, personal hygiene, use of potable water and proper use of latrine should be given due attention to prevent and control parasitic infections among children in both urban and rural areas.